The Effectiveness of behavioral activation group therapy on the symptoms of depression, anxiety, and quality of life in medical students - Parisa Rezapour; Maryam Bakhtiari; Abbas Masjedi-arani; Amirsam Kiani-moghadam4 (فصلنامه ابن سینا)
Background: Considering the importance of depression is student groups and its effect on their academic achievements, this study was conducted to investigate the effectiveness of behavioral activation group therapy on the symptoms of depression, anxiety, and quality of life in the students’ Jundishapur University of Medical Sciences. Materials and methods: The current research design was quasi-experimental with pretest, posttest, and the control group. After clinical evaluations and qualifications, 30 medical students were selected randomly, and then replaced in two groups of experimental and control of 15 subjects. The experimental group received the behavioral activation therapy in 8 sessions; however, the control group received no interventions. The Beck Depression Inventory (BDI-II), the Beck Anxiety Inventory (BAI), and Short Quality of Life Questionnaire (SF-36) were used to collect data. The multivariate analysis of variance was employed to analyze data. Results: The results indicated that the experimental and control groups were significantly different from each other in terms of depression, anxiety, and quality of life (p<0.001). In other words, the level of depression and anxiety declined significantly in the experimental group compared with pretest and the control group; however, the quality of life increased in the experimental group. Conclusion: The present study indicated that behavioral activation therapy would be an appropriate treatment for medical students to reduce the symptoms of depression and anxiety and increase their quality of life.